Predictors of academic success in postgraduate auditing in the Chartered Accountancy programme at a South African university - Crous, C.; Goodchild, E. (South African Journal of Higher Education, 2021)
South African universities that offer the accredited Chartered Accountancy [CA] programme are monitored by the South African Institute of Chartered Accountants (SAICA) to ensure that the programme meets SAICA’s requirements in terms of the standards of teaching and learning. The monitoring includes a scrutiny of the academic success of students with regard to pass rates and throughput rates. This inevitably results in universities not only focussing on the academic success of students, but also predicting the success of their students. Much of the existing research focusses on the success of first-year students in the subject field of financial accounting, or success overall at postgraduate level. This article aims to bridge the gap in the research field by exploring academic predictors of success for postgraduate students in the accounting programme, with reference to a specific module ‒ namely, auditing ‒ at a South African university over a period of five years (2014‒2018). The objectives are to determine the extent to which selected grade-12 subjects (maths and language); admission requirements, namely the Admission Point (AP) score and the National Benchmark Test (NBT); as well as undergraduate performance could predict the success of a postgraduate module. Drawing on quantitative data, the findings indicate that the grade-12 subjects and admission requirements do not have a positive correlation with academic success, with only a few selected undergraduate level modules predicting academic success.